Negative Affective Responses to Stress among Urban Police Officers: A General Strain Theory Approach. Issue 6 (3rd June 2019) - Bishopp, Stephen A; Piquero, Nicole Leeper; Worrall, John L; Piquero, Alex R
ABSTRACT: The larger literature on police stress indicates that much of their stress emanates from two sources: organizational and environmental. These sources coexist in officers' lives but function differently across police agencies. Officer experiences with stress also tend to lead to emotional reactions, some of which can be negative and increase the risk of misconduct. Agnew's general strain theory provides one useful theoretical framework within which the relationship between officer strain and negative emotions can be investigated. Using data from three urban Texas police agencies, this study investigates the main sources of police strain as predictors of anger, depression, and burnout. Further, differences in negative emotions across agencies are also examined. Results show that organizational stress is significantly related to all three negative emotions across agencies. Implications and future research directions are highlighted.